2014
DOI: 10.1039/c4ra09673h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of amino acid-modified adsorption resins and their adsorption properties in the purification of tabersonine from Voacanga africana seeds

Abstract: The modified MARs had good adsorption of impurities but poor adsorption of tabersonine from extracts of Voacanga africana seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This result revealed that citric acid was successfully anchored on resins. In addition, the absorption band in the vicinity of 678 cm −1 still existed in curves a1, which indicated that the –Cl groups were not fully substituted by citric acid during the reaction [ 17 , 18 ]. Curves b1, b2 and b3 in figure 3 are the FTIR spectra of PS-Cl, PS-OH and PS-O-CA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This result revealed that citric acid was successfully anchored on resins. In addition, the absorption band in the vicinity of 678 cm −1 still existed in curves a1, which indicated that the –Cl groups were not fully substituted by citric acid during the reaction [ 17 , 18 ]. Curves b1, b2 and b3 in figure 3 are the FTIR spectra of PS-Cl, PS-OH and PS-O-CA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained PS‐( S )‐BINAP resin was then shaken with [(CH 3 CN) 4 Cu]PF 6 in 1, 2‐dichloroethane for 24 h. After filtering, PS‐CuPF 6 ‐( S )‐BINAP resin was obtained. The content of chloromethyl in PS‐Cl was determined by an electrochemistry method that was described in our previous work . The content of BINAP in resin could be obtained by determining the content of phosphorus in BINAP loaded resin.…”
Section: Methodsmentioning
confidence: 99%
“…Schemes for the preparation of resin with chloromethyl groups (PS‐Cl) and resin with CuPF 6 ‐( S )‐BINAP complexes (PS‐CuPF 6 ‐( S )‐BINAP) are shown in Figure . The resin with chloromethyl groups (PS‐Cl) was synthesized using the method described in our previous work . 5, 5′‐diamino‐BINAP was synthesized referring the prior art treatise .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations